Validity of Artificial Intelligence-Based Interactive Chatbot Learning Media in Elementary School Science and Social Studies (IPAS) Learning - Rozik Arional Prinata; Novialita Angga Wiratama; Wendri Wiratsiwi (FIP Unimed, 2026)
Science and Social Studies (IPAS) learning in elementary schools is still predominantly supported by conventional learning media, resulting in limited student engagement during the learning process. This study aimed to determine the validity of an Artificial Intelligence-based interactive learning media for fifth-grade IPAS learning at SD Negeri 01 Sedayulawas. The validation process involved three validators: a media expert, a subject matter expert, and an elementary school practitioner. The study employed a Research and Development (R&D) approach using the ADDIE model. The learning media was developed through Canva and integrated with an AI-powered chatbot. Media validity was evaluated by media experts, subject matter experts, and education practitioners using a Likert-scale assessment. The results indicated that the developed media achieved a very valid category across the aspects of presentation, content, organization, and language. Therefore, the Artificial Intelligence-based interactive learning media is considered valid and suitable for use as an alternative learning resource for IPAS in elementary schools.